2019
DOI: 10.5937/aaser1948097m
|View full text |Cite
|
Sign up to set email alerts
|

Role of rootstock and apple fruit tissue in antioxidant activity

Abstract: During two consecutive years (2018 and 2019) we investigated the effect of two clonal rootstocks on fruit weight, contents of some non-nutrients and total antioxidant capacity (TAC) in the flesh and peel of cv. 'Hapke' apple. Results showed that fruit weight was significantly higher on M.9 T337 than on M.26 rootstock and similar in both 2018 and 2019. M.26 rootstock significantly improved titratable acidity (TA), vitamin C content, total phenolic content (TPC), total flavonoid content (TFC) and TAC in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Similar tendencies were found by Marini et al (2002), who reported that M.9 showed the best effect on the FW of 'Gala' compared to 7 dwarfing rootstocks. We also found a positive effect of M.9 on this trait in our earlier study on apple (Milošević et al, 2019). According to Cripps et al (1993), 'Pink Lady' fruits are medium to large in size (70 to 75 mm average diameter).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Similar tendencies were found by Marini et al (2002), who reported that M.9 showed the best effect on the FW of 'Gala' compared to 7 dwarfing rootstocks. We also found a positive effect of M.9 on this trait in our earlier study on apple (Milošević et al, 2019). According to Cripps et al (1993), 'Pink Lady' fruits are medium to large in size (70 to 75 mm average diameter).…”
Section: Resultssupporting
confidence: 70%
“…Soil and weather conditions for this area were explained in our earlier study on apple (Milošević et al, 2019).…”
Section: Plant Materials and Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, mineral composition of fruits is associated with the ability to store and maintain texture, and the incidence of physiological disorders that depreciate the quality of apples (MIQUELOTO et al 2011, AMARANTE et al 2012, CORRÊA et al 2012. In addition, according to some authors, functional properties of fruits, such as antioxidant capacity and total phenolic compounds, can also be affected by the rootstock (REMORINI et al 2008, KVIKLYS et al 2014, MILOŠEVIĆ et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit quality is determined by a large series of physiological changes which are genetically programmed to render the fruit more attractive to impact consumer appreciation, i.e. the fruit becomes softer, sweeter, more coloured and more aromatic throughout the phase of ripening (Giovannoni, 2001;Busato et al, 2016;Milošević et al, 2019). Apple fruits are climacteric in nature; therefore, physiological and biochemical processes are governed by the enzymes whose activity is triggered and coordinated by ethylene.…”
Section: Introductionmentioning
confidence: 99%